Male Infertility: Diagnostic and Epidemiological Aspect Concerning 96 Cases in a Teaching University Hospital of Cotonou, Benin Republic - HOUNNASSO, PRINCE PASCAL; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; DANKORO, Abdoudjalilou Sanni; SOUMANOU, Fouad Kolawale Yde; NATCHAGANDE, GILLES; AGOUNKPE, M. M.; TORE SANNI, R. (My University, 2015)
Objectives: The goal of this study is to describe the epidemiological and diagnostic aspect of male infertility in the Department of Urology and Andrology of the Hospital mentioned above. Methods: This was a retrospective descriptive study of 6 months duration at the Academic Clinic of Urology and Andrology of a Teaching Hospital in Cotonou. A total of 96 medical records of patients were retrieved for the study. Results: The average age of the patients was 37.2 ± 6.7 years old. About 59.4% of the cases were primary infertility. The average duration of the infertility was 51 months. From the patients past medical histories; 44.9% suffered from gonorrhea. On clinical examination, the findings were: Varicocele in 23% of the cases, testicular hypotrophy in 9.3% and epididymal cyst in 4.6%. The seminal fluid analysis revealed hypospermia in 30.1% of cases, azoospermia in 33.7%, asthenozoospermia in 75.5% and teratozoospermia in 61.5%. The pH was basic in 46.4% of the cases. Follicular stimulating hormone and testosterone levels were high in 48.1% and 12.5% of cases, respectively. About 31.6% of the cases had the positive chlamydial serological test. Semen culture was positive in 25% of the cases and the main organism isolated was Staphylococcus aureus in 66.6% of the cases. Conclusion: Male infertility is the cause of couple infertility in around a third of the cases. In this study, we have found various etiologies of causes of male infertility. However, idiopathic causes could be found.
Keywords: Cotonou; etiology; hormonal profile; male infertility; semen analysis